(untitled) (International Journal of Food and Nutritional Sciences, 2021)
India, with its rich tapestry of artistic expression and linguistic diversity, spans from traditional to contemporary realms. Various art forms have carved out a significant niche, attracting both art enthusiasts and language scholars. The nexus between Madhubani art and Indian mythology is both profound and intriguing. The artistic and cultural outputs of India’s tribal and rural communities have established a distinguished presence among art connoisseurs nationwide.